Application of Double-Skin Facade (DSF) in tropical climate countries: a case study of Suasana PJH Tower in Putrajaya - Nur Syazwani Sahira Nor Faizalasdi,; Khairul Asyraf Mohd Rodzi, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Double skin facade (DSF) is often heard and easily found in cold climate countries. For those countries, DSF are often used for heating mechanism to avoid heat loss. The solar-heated air contained in the cavity can heat the space outside the glass, reducing the need for an internal heating system. Due to the scorching sun that causes hot temperatures every day, DSF is rarely detected and be applied in tropical climate countries. However, DSF can still be used in the tropical climates with some modification to its parameters. The aim for this paper is to investigate the application of double skin facade in the tropical climate countries. Literature review on several resources such as journal, proceedings, book, and web surfing are conducted. Suasana PJH tower, Putrajaya that applied DSF in the building was selected as a case study. From the research, it can be concluded that DSF can be beneficial, but at the same time, can be a problem depending on the application of the DSF. The result for this research will be a reference and a guidance for researcher to design a building with proper application of the DSF.